2019
DOI: 10.3390/ijms20020298
|View full text |Cite
|
Sign up to set email alerts
|

Homeostasis of Glucose and Lipid in Non-Alcoholic Fatty Liver Disease

Abstract: Industrialized society-caused dysregular human behaviors and activities such as overworking, excessive dietary intake, and sleep deprivation lead to perturbations in the metabolism and the development of metabolic syndrome. Non-alcoholic fatty liver disease (NAFLD), the most common chronic liver disease worldwide, affects around 30% and 25% of people in Western and Asian countries, respectively, which leads to numerous medical costs annually. Insulin resistance is the major hallmark of NAFLD and is crucial in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(70 citation statements)
references
References 134 publications
(152 reference statements)
4
63
1
2
Order By: Relevance
“…The impact of chronic liver disease on hepatic lipid metabolism has been mentioned in several studies (10,11). One important nding in this study is that patients with severe NAFLD, as indicated by a FIB-4 score greater than 2.67, were found to have lower lipid levels, speci cally total cholesterol and LDL, than patients with moderate and mild FIB-4 scores.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The impact of chronic liver disease on hepatic lipid metabolism has been mentioned in several studies (10,11). One important nding in this study is that patients with severe NAFLD, as indicated by a FIB-4 score greater than 2.67, were found to have lower lipid levels, speci cally total cholesterol and LDL, than patients with moderate and mild FIB-4 scores.…”
Section: Discussionsupporting
confidence: 49%
“…Another interesting nding is that fasting glucose was higher in the mild versus moderate NAFLD group (p < 0.05), as shown in Table 1. Although the relationship between the metabolism of glucose and chronic liver disease is not fully understood, there have been several proposed mechanisms for glucose homeostasis in NAFLD (11). A possible explanation for a lower fasting glucose in moderate versus mild NAFLD group is that the liver's ability to mobilize and distribute glucose to peripheral tissues is diminished, this is especially seen in patients with cirrhosis where their liver is severely dysfunctional (14).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, during NAFLD pathogenesis, hepatic steatosis occurs when fatty acid uptake and synthesis exceed oxidation and re‐secretion . In addition, downregulation of glycolysis and glycogen synthesis can also represent the manifestation of insulin resistance, which is closely related to NAFLD development . Therefore, these HBV‐related metabolic changes may participate in the occurrence of NAFLD.…”
Section: Possible Mechanistic Role Of Hbv Infection In Nafld Pathogenmentioning
confidence: 99%
“…In the normal physiological status, high level of glucose promotes the secretion of insulin, activates carbohydrate-responsive elementbinding protein (ChREBP), and meanwhile, provides substrate to facilitate lipogenesis in the liver . In terms of insulin, it activates sterol regulatory element-binding protein 1c (SREBP-1c) to up-regulate lipogenic enzymes, and then promotes de novo lipogenesis (Eissing et al, 2013;Chao et al, 2019). Figure 2 shows the overview of lipogenesis in hepatocytes.…”
Section: Reducing Hepatic De Novo Lipogenesismentioning
confidence: 99%